Knowledge of Idiomaticity: Evidence from Idiom Calquing and Folk Literalization - He, Zili (Kansas Working Papers in Linguistics, 1990)
To the synchronic linguistic analyst, an idiom is, by nature, semantically noncompositional. However, the language-user-in-culture may know (among other things) how the association between the nonliteral and the literal meanings of an idiom is culturally motivated. This paper looks at such cultural knowledge of idiomaticity, with evidence from IDIOM CALQUING-- the literal borrowing of idioms across languages, and FOLK LITERALIZATION--the re-creation of literal meanings for idioms.